PERCEPTION OF PEOPLE TOWARDS THE LOCAL PARKS IN NEPAL - Ballav Niroula (STIE Mahardhika, 2023)
The main objective of this research is to evaluate the perception of people towards the local parks in Lalitpur, Bhainsepati, Nepal. For this, people’s perceptions towards environmental, economic, and health factors are considered. Perceptions of people are abstract and cannot be measured directly. This study aims to measure people’s perceptions using a structured questionnaire. A total of 215 questionnaires were distributed to the respondent and only 170 respondents’ responses were received and used in this study. Using descriptive research design data were described and analyzed. A convenience sampling technique was applied to select the sample from the unknown population. Data has been analyzed and interpreted by statistical tools to find the results. The study found that people have a positive and significant attitude toward the environmental, economic, and health factors in the local parks. It has been also found that; public participation, cleanness, and proper sanitation are essential for the local parks.